อัตลักษณ์อีสานในเพลงลูกทุ่งของ ไผ่ พงศธร - กนกพร เล็งศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This thesis investigates Isan identities in Phai Phongsathorn’s luk-thung songs. It employs the concept of “identity” as a key analytical tool in its examination of 45 songs from 7 albums by Phai Phongsathorn from 2005 to 2012. The thesis comprises six chapters. Chapter one is an introduction. Chapter two offers the background knowledge about luk-thung songs and luk-thung Isan songs. Chapter three analyses “Isan” as a discourse. Chapter four and five examine Phai Phongsathorn’s songs by topics. Chapter four discusses Isan people and their relationship with traditional values as well as value negotiation. Chapter five focuses on Isan people and their fighting spirit. Chapter six offer a conclusion of the study and suggestions for future studies. The analyses of Isan identities in Phai Phongsathorn’s luk-thung songs show that identity of Isan people is adaptable to the changing time, mode of production and social changes. Isan identity is, therefore, dynamic and adjustable to factors such as economic necessities and changing means of livelihood which present Isan communities and cultures with new challenges. The dynamism and ability to adapt to a new social environment as shown in Phai Phongsathorn’s songs prove that Isan identities are resulted from the process of selection, negotiation and making use of traditional values as cultural capital in order to lead one’s life in an ever changing society. More importantly, Isan identities studied here resist prejudices against and deprecation for Isan people from some sectors of the society.